Intelligence structure of 16–18 years old intellectually gifted students - Šimelionienė, A.; Gintilienė, G. (Psichologija, 2011)
The article analyses the intelligence structure of 16–18-year-old gifted students. Previous findings have indicated that high IQ individuals show more subtest scatter and a large discrepancy between abilities and very highly developed skills in some modalities, with many other cognitive skills being average or just slightly better. So, intelligence structure and subtests analysis, rather than IQ, became the focus of interpretation, and a multidimensional view of intelligence, provides a greater insight into the nature of human abilities than do summary intellectual indexes. Intelligence Structure Test 2000R (I-S-T 2000 R, Amthauer et al., 2001) was administrated in a group setting to 209 students aged 16–18 years from two schools in different Lithuanian towns. Data from 29 intellectually gifted students with Reasoning Total score 95 percentile and higher were included for analyses of intelligence structure. The exploratory factor analysis was applied to the I-S-T 2000 R basic module scores of intellectually gifted students to evaluate the validity I-S-T 2000 R for this population. A three-factor solution that mirrored the numerical, figural and verbal factors of the I-S-T 2000 normative sample appeared to be the most supportable. Intellectually gifted students had higher intellectual abilities, knowledge and memory skills than their peers. The mean of I-S-T 2000 R scale and subtest scores for this sample of gifted students was considerably above the normative mean. The significant differences in scores between gifted and norm groups were found for Calculations and Number Series subtests. Fluid (Gf) and Crystallized (Gc) Intelligence, Numerical (N) and Verbal (Vb) Intelligence discrepancies (Gf > Gc and N > Vb) for gifted students group were significantly greater discrepancies obtained in the standardization sample. Intellectually gifted students’ Verbal Memory scores wel significant higher Visual Memory scores and their Figural Knowledge scores was significantly higher than the Verbal Intelligence and Numerical Intelligence scores. The gifted students’ intellectual strengths are mathematical abilities, abilities to calculate, inductive and logical reasoning.